2013
DOI: 10.1111/1477-8947.12005
|View full text |Cite
|
Sign up to set email alerts
|

“How far do you have to walk to find peace again?”: A case study of First Nations' operational values for a community forest inNortheastBritishColumbia,Canada

Abstract: In this paper we report upon research conducted with two First Nations located in British Columbia, Canada (Saulteau First Nations and West Moberly First Nations) on their preferences regarding forest operations within their community forest license. We confirmed the forestry‐related values previously documented in other research, and we are able to determine specific parameters with regard to the protection or integration of these values, particularly those that are ecologically based. In addition, we identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Similarly, Lewis and Sheppard (2006) have demonstrated that generational differences exist in the ways that youth and Elders interact with, and accept, various support tools, such as maps and landscape visualization software that are used in forest resource decision-making. Because traditional outcomes of forest development, such as capacity-building arrangements , employment opportunities (Zurba and Trimble 2014), or cultural-retention initiatives (Booth and Muir 2013) are often targeted towards Indigenous youth, these differences in perspectives may result in such opportunities being unbeneficial or undesirable to youth, as they are created on youths' behalf, but without their direct input. thermore, any collaborative arrangements developed without the direct input of youth run the risk of becoming irrelevant over time, as younger generations enter community leadership roles (Zurba and Trimble 2014).…”
Section: Broad Community Engagementmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, Lewis and Sheppard (2006) have demonstrated that generational differences exist in the ways that youth and Elders interact with, and accept, various support tools, such as maps and landscape visualization software that are used in forest resource decision-making. Because traditional outcomes of forest development, such as capacity-building arrangements , employment opportunities (Zurba and Trimble 2014), or cultural-retention initiatives (Booth and Muir 2013) are often targeted towards Indigenous youth, these differences in perspectives may result in such opportunities being unbeneficial or undesirable to youth, as they are created on youths' behalf, but without their direct input. thermore, any collaborative arrangements developed without the direct input of youth run the risk of becoming irrelevant over time, as younger generations enter community leadership roles (Zurba and Trimble 2014).…”
Section: Broad Community Engagementmentioning
confidence: 99%
“…This may prove to be a difficult task however, as current forest management systems largely reflect Western worldviews (McGregor 2011) with strong colonial legacies (Bouman et al 1996), and the assumption that ultimate authority rests with provincial governments (Mabee and Hoberg 2006). Consequently, there remains a strong need to develop processes that incorporate Indigenous values and interests into forest management, as well as provide communities with meaningful opportunities to occupy a more influential role in forestry-related decisionmaking frameworks.…”
Section: Flexible and Holistic Management Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence from the US highlights that forestry can support community members through job creation, and income from harvesting may help groups achieve goals of self-governance and self-sufficiency (Trosper 2007). However, other research shows that involvement in the forestry sector can cause conflict as economic, social, cultural, spiritual, and ecological values collide (Booth and Muir 2013;Booth and Skelton 2011). This view is consistent with a critical perspective of development in which scholars see development as a "negative" transformative process, e.g., nature and forests become commodities, traditional value systems are cast as primitive, and indigenous communities must assimilate with the market to enhance their standard of living (Escobar 1995).…”
Section: Literature Reviewmentioning
confidence: 99%